Distribución y ciclo vital de tres especies del género Hydraena en Nicaragua (Coleoptera: Hydraenidae) - Delgado, Juan A. (1996)
Three species of lhe genus Hydraena: H. collymba, H. malkini and H.particeps are reported by the first time from Nicaragua. Lasvae of H. Particeps were reared from eggs laid in captivity. Oviposition occured during 2-3 days after mating. The Ist, 2nd and 3r laral slages wcrc completed in about 17 days. The average developmental period of H. particeps(egg to adult) was estimated in three weeks. This is the first known live cycle of these species belonging to the family Hydraenidae from tropical regions.